THE PUBLIC LIBRARY OF THE FUTURE - NIKTA, MARINA; Karydis, Christos (Qualitative and Quantitative Methods in Libraries, 2021)
The design of the library environment must take into account all the parameters that affect the smooth use of the library. The study of human capabilities, limitations and limits in relation to the work environment and the adaptation of work to man through the discovery-diagnosis-solution of working pressures and unpredictable events that adversely affect his performance, is a factor that determines the degree of success of the role of the Municipal Library in the local community. Creating a good working environment is a basic condition for development and proper library operation. As long as safety and working conditions both improve, problems are reduced and the library responds to its role. Given the relationship and importance the physical space in which a library is housed has for its development, it is obvious that the user who will use its services is the one who benefits from the correct organization of the space and the functions in a library.